Rock around DYRK1A: Ethnic diversity, clinical challenges. Issue 5 (11th February 2023) - Moroni, Alice; Pezzani, Lidia; Alfei, Enrico; Scatigno, Agnese; Cereda, Anna; Marzaroli, Michela; Guuva, Claudia; Gabbiadini, Sara; Pezzoli, Laura; Marchetti, Daniela; Spaccini, Luigina; Iascone, Maria
Abstract: DYRK1A ‐related intellectual disability is a recently described syndrome characterized by microcephaly, global developmental delay, impaired speech development, and distinctive facial features, which let to define it as a recognizable syndrome. Here we report four new patients of different ethnicity, broadening the clinical phenotype of the condition and highlighting how ethnic influences in the facial appearance could make it less recognizable.